(3GdQMdI ef aGS Edi MVQehJs - (3jhSa Hf YGHO GdGOQjSj,J (B1044 (3g` s
(3ChdgG (B:s
(3CeG HYO , agPG edJbW ef GdcJGH GdeSei HGdQMdI bGd GdSjO jhSa Hf YHGO GddEOQjSi fSHkG GdaGSi hWfkG , YeQ Gddg HhLhOg eYGde GdOjf hCMjG HYdheg GdeajOI SfI LOg s
(3BNQgG (B:s
(3dCfg de jbd jhekG QH EaQ di NWjFJi jhe GdOjf GfJgi GdebUhO hGdTF HGdTF jPcQ s
(3HgG fXGe GdJYbjHIs
(3edJbW efgGs
(3cJHJ HYV GdYfGhjje HGdMeQI s
(3dYdgG cJHJ ai YUQ GdeDda Ch HYOg Hbdjd s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa eLehYg GdcGa (B((3QMdGJ (B320) s
Keywords: (3GdLZQGajG h GdHdOGfs